Hemodynamic analysis of fast and slow aneurysm occlusions by flow diversion in rabbits. (20th October 2014) - Chung, Bongjae; Mut, Fernando; Kadirvel, Ramanathan; Lingineni, Ravi; Kallmes, David F; Cebral, Juan R
Abstract : Purpose: To assess hemodynamic differences between aneurysms that occlude rapidly and those occluding in delayed fashion after flow diversion in rabbits. Methods: Thirty-six elastase-induced aneurysms in rabbits were treated with flow diverting devices. Aneurysm occlusion was assessed angiographically immediately before they were sacrificed at 1 (n=6), 2 (n=4), 4 (n=8) or 8 weeks (n=18) after treatment. The aneurysms were classified into a fast occlusion group if they were completely or near completely occluded at 4 weeks or earlier and a slow occlusion group if they remained incompletely occluded at 8 weeks. The immediate post-treatment flow conditions in aneurysms of each group were quantified using subject-specific computational fluid dynamics and statistically compared. Results: Nine aneurysms were classified into the fast occlusion group and six into the slow occlusion group. Aneurysms in the fast occlusion group were on average significantly smaller (fast=0.9 cm, slow=1.393 cm, p=0.024) and had smaller ostia (fast=0.144 cm 2, slow=0.365 cm 2, p=0.015) than aneurysms in the slow occlusion group. They also had a lower mean post-treatment inflow rate (fast=0.047 mL/s, slow=0.155 mL/s, p=0.0239), kinetic energy (fast=0.519 erg, slow=1.283 erg, p=0.0468), and velocity (fast=0.221 cm/s, slow=0.506 cm/s, p=0.0582). However, the differences in the latter two variables were only marginally significant. Conclusions: Hemodynamic conditions after flow diversion treatment of cerebral aneurysms in rabbits are associated with the subsequent aneurysm occlusion time. Specifically, smaller inflow rate, kinetic energy, and velocity seem to promote faster occlusions, especially in smaller and small-necked aneurysms. These results are consistent with previous studies based on clinical series.